2010
DOI: 10.1053/j.gastro.2010.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Gastrointestinal Polyps and Colorectal Adenocarcinomas in a Prospective Series of PTEN Mutation Carriers

Abstract: BACKGROUND & AIMS Germline PTEN mutations cause Cowden syndrome (CS), associated with breast and thyroid cancers. Case reports found 35–85% of CS patients had gastrointestinal (GI) hamartomas. The association of benign and malignant GI neoplasias with CS remains debatable. Our goal is to describe the GI phenotype in a prospective series of PTEN mutation carriers. METHODS Patients who met relaxed International Cowden Consortium criteria (N=2548) or with ≥5 GI polyps, ≥1 of which was hyperplastic or hamartomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
217
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(245 citation statements)
references
References 22 publications
9
217
2
7
Order By: Relevance
“…[24][25][26][27][28] Clinical diagnostic criteria involve combinations of major and minor criteria 29 ( Table 4). We recommend referral for anyone meeting any three criteria from the major or minor diagnostic criteria.…”
Section: Cowden Syndrome Also Known As Pten Hamartoma Tumor Syndromementioning
confidence: 99%
“…[24][25][26][27][28] Clinical diagnostic criteria involve combinations of major and minor criteria 29 ( Table 4). We recommend referral for anyone meeting any three criteria from the major or minor diagnostic criteria.…”
Section: Cowden Syndrome Also Known As Pten Hamartoma Tumor Syndromementioning
confidence: 99%
“…Instead, true intestinal ganglioneuromas are found in neurofibromatosis type 1 and multiple endocrine neoplasia type 1 [Ledwidge et al, 2007]. Intestinal lipomas, hyperplastic and, less commonly, adenomatous polyps can also occur [Heald et al, 2010].…”
Section: Pten Hamartoma Tumor Syndrome(s) (Phts)mentioning
confidence: 99%
“…The number of polyps can range from none to innumerable, while their incidence is unknown; in a recent study 95% of in PTEN mutation carriers subjected to colonoscopy were found to have intestinal polyps [Heald et al, 2010].…”
Section: Pten Hamartoma Tumor Syndrome(s) (Phts)mentioning
confidence: 99%
See 1 more Smart Citation
“…This risk has not been quantified sufficiently 63,64], but certainly warrants endometrial cancer screening.…”
Section: Other Cancer Syndromesmentioning
confidence: 99%